2012
DOI: 10.1002/ps.3357
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterisation and expression profiling of the cDNA encoding the ryanodine receptor in diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae)

Abstract: There are at least two alternative splices of PxRyR expressed in all developmental stages and tissues in P. xylostella at various levels. The results provided the basis for further understanding of the mechanisms of resistance to diamide insecticides in P. xylostella.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…As with other published data for insects, we found that the egg stage generally is the lowest expression level of RyR mRNA during the different developmental stages, just like in T. castaneum [48], B. dorsalis [32], H. armigera [42], O. furnacalis [17], Sogatella furcifera [47], and L. decemlineata [31]. In C. suppressalis, CsRyR expression level is highest in 3 rd instar larvae and much lower in eggs, 6 th instar larvae and adults, which is similar to but not the same as the RyR mRNA expression in P. xylostella [14,39] and D. melanogaster [49].…”
Section: Accepted Manuscriptmentioning
confidence: 84%
See 4 more Smart Citations
“…As with other published data for insects, we found that the egg stage generally is the lowest expression level of RyR mRNA during the different developmental stages, just like in T. castaneum [48], B. dorsalis [32], H. armigera [42], O. furnacalis [17], Sogatella furcifera [47], and L. decemlineata [31]. In C. suppressalis, CsRyR expression level is highest in 3 rd instar larvae and much lower in eggs, 6 th instar larvae and adults, which is similar to but not the same as the RyR mRNA expression in P. xylostella [14,39] and D. melanogaster [49].…”
Section: Accepted Manuscriptmentioning
confidence: 84%
“…However, Guo et al [14] deduced that both P. xylostella RyRs may have a similar function and this phenomenon might be attributed to the alternative splicing of mRNA or the diversity of insect RyRs. To date, splicing variants have been observed in several insects, such as P. xylostella [39], Heliothis virescens [41], C. medinalis [15], Helicoverpa armigera [42], O. furnacalis [17], and D. melanogaster [18].…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 3 more Smart Citations